SALAK FRUIT (SALACCA ZALACCA) POTENTIAL FOR CITRIC ACID PRODUCTION USING ASPERGILLUS NIGER - Ayu Mungkashi, Galuh
The most commonly known species of salak is Salacca zalacca. In Tasikmalaya area, this variety is known as Salak Manonjaya. Its popularity progressively decreased compared to the other type of salak fruit. This condition is very worrying and will cause the loss of this variety in the future. Carbohydrate content of salak fruit reaching 20.90% and its productivity reaching 105,321 quintals / year in Tasikmalaya, making it suitable to be substrate in the process of citric acid fermentation. The use of salak as a substrate for citric acid production will be one of new alternatives in the use of salak fruit which comes from Tasikmalaya area. Aspergillus niger is known to produce citric acid with glucose as the main substrate. Glucose can be obtained from carbohydrates hydrolysis by amylase enzyme. This research aims to determine the potential of salak fruit with rice bran to produce citric acid using A. niger with Solid State Fermentation (SFF) method.